Trends in hypertension prevalence, awareness, treatment, and control in the Thai population, 2004 to 2020 - Wichai Aekplakorn; Suwat Chariyalertsak; Pattapong Kessomboon; Sawitri Assanangkornchai; Surasak Taneepanichskul; Allison Goldstein; Danielle Cazabon; Nareemarn Neelapaichit; Obehioye Aimiosior (BMC, 2024)
Abstract Background Under Thailand's universal health coverage every citizen has access to primary care including free hypertension treatment. This study describes temporal trends in hypertension prevalence, awareness, treatment, and control in Thailand. Methods Data were analyzed from four survey cycles of Thailand's National Health Examination Survey (NHES), between 2004 and 2019-2020. The NHES is a nationally-representative cross-sectional survey conducted every five years using a multistage probability sample. Hypertension was defined as systolic blood pressure > = 140 or diastolic blood pressure > = 90 mmHg or currently taking antihypertensive medicines; blood pressure control was defined as < 140/90 mmHg for patients without diabetes and < 130/80 mmHg for those with diabetes. Results In 2019-2020, age-standardized hypertension prevalence in Thailand was 25.7% (24.6% females, 26.8% males). Among people with hypertension, 51.5% were aware of their diagnosis, 47.9% were treated, and 22.7% had controlled blood pressure. Age-standardized hypertension prevalence remained relatively unchanged in Thai adults from 2004 to 2019-2020, however trends varied by age group. Hypertension control increased from 8.8% in 2004 to a peak of 30% in 2014 but dropped to 22.7% by 2019-2020. Hypertension awareness increased from 30.7 to 55.8% between 2004 and 2014, but decreased to 51.5% by 2019-2020. Conclusion Hypertension prevalence in Thailand has remained high over the past 15 years. Despite universal health coverage, hypertension awareness has not improved and blood pressure control has decreased in the past five years. An urgent and concerted public health response is needed to improve diagnosis and control of hypertension to prevent avoidable cardiovascular disease.